WATER SOLUBILITY IN HAPLOBASALTIC MELTS - Benne D.; Behrens H. (My University, 2003)
The solubility of water in melts of the haplobasaltic system (NaAlSi3O8-CaAl2Si2O8-CaMgSi2O6, Ab-An-Di) was investigated at pressures of 50, 200 and 500 MPa and at temperatures between 1200degreesC and 1420degreesC using an internally heated gas pressure vessel. Compositions close to the binary joins Ab(100)-An(100) and Ab(50)Di(50)-An(50)Di(50) were studied. The water content of the glasses was analysed using Karl-Fischer-titration and near-infrared (NIR) spectroscopy. Linear molar absorption coefficients for the NIR combination bands of OH groups at 4500 cm(-1) (epsilon(OH)) and molecular H2O at 5200 cm(-1) (epsilonH(2)O) were determined for Ab(50)An(50), An(56)Di(44), and Ab(54)Di(46) compositions. Concentration of OH groups is found to be significantly higher in Ab(50)An(50) glasses than in other glasses quenched at similar rate. This is attributed to the depolymerisation of the network structure enabling the formation of stable Ca-complexes in the glasses. An increase in pressure from 50 to 200 or from 200 to 500 MPa approximately doubles the water solubility in haplobasaltic melts. Depending on compositions 2.0-3.0 wt% water can be dissolved at 50 MPa, 3.7-6.1 wt% at 200 MPa and 7.6-12.4 wt% at 500 MPa. In general, the lowest H2O solubility was found in the An(56)Di(44) melt. At 50 MPa, the variation of water solubility with composition appears to be complex but the precision of the data does not allow to extract reliably compositional trends. In general, data at 200 and 500 MPa show a strong decrease in H2O solubility with increasing Di content, e.g. from 5.99 wt% (Ab(100)) to 4.94 wt% (Ab(54)Di(46)) and from 5.81 wt% (Ab(50)An(50)) to 5.21 wt% (Ab(27)An(29)Di(44)) at 1200degreesC/200 MPa. The effect of Ab/An ratio on water solubility appears to be small at 200 MPa. In contrast, at 500 MPa the water solubility decreases strongly with increasing An content of the melt.